Slovenski narod v dobi zgodnje mediatizacije - Pušnik, Maruša (Teorija in praksa, 2018)
This paper examines how the newspaper Slovenski narod, a central Slovenian media outlet in the second half of the 19th and first half of the 20th centuries, responded to radical changes in the media landscape accompanying electrification and industrialisation. These changes came during the second wave of mediatisation, which started in the Slovenian space with the introduction of electronic media and drastically altered the entire media landscape. The article examines how Slovenski narod faced these considerable media changes. For a detailed case study, I chose the arrival of cinema at the end of the 19th century and studied how Slovenski narod discussed its first appearance and widespread entry into Slovenian society. I was interested in the discursive frame built by Slovenski narod around the arrival of cinema because we may also make conclusions based on this regarding how the press has responded to other radical, more intense changes to the media occurring later in the 20th century upon the introduction of electronic media (first radio and then television).
Keywords: elektrifikacija; History of journalism; kino; kulturne transformacije; mediatizacija; Slovenian newspapers; Slovenski časniki; Slovenski narod (periodična publikacija); Zgodovina novinarstva